Linguistische Methodenreflexion im Aufbruch Beiträge zur aktuellen Diskussion im Schnittpunkt von Ethnographie und Digital Humanities, Multimodalität und Mixed Methods - Meiler, Matthias; Siefkes, Martin (Linguistik - Impulse & Tendenzen, 2023)
A focus on methods can currently be observed in all subfields of linguistics. The book brings together the current discussion of methods and assembles contributions that move along the spectrum of ethnography, mixed methods, and digital humanities.